Aspectos biológicos de cycloneda sanguinea (coleoptera: Coccinellidae) alimentadas con pulgones criados en algodón transgénico bollgard ® - Funichello, Marina [UNESP]; Costa, Lílian Lúcia [UNESP]; Gil, Oniel Jeremías Aguirre [UNESP]; Busoli, Antonio Carlos [UNESP] (My University, 2012)
Cycloneda sanguinea is an important biological control agent of aphid cotton. The objective of this study was to evaluate the biological aspects of C. sanguinea fed with nymphs and adults of Aphis gossypii reared in DeltaOPAL and NuOPAL cultivars (Bollgard I). The experiment was conducted in the laboratory under controlled temperature (25 ± 1°C), humidity (70 ± 10%) and photophase (12 hours). The experimental design was completely randomized, and treatments aphids fed on the two cultivars, and replicates 40 individuals. Each larva was individually until adult emergence of the predator in Petri dishes of 9 cm in diameter with moistened filter paper. For evaluation of individual adults were five couples newly emerged in plastic pots 12 cm in diameter and 9 cm tall, with filter paper for oviposition. The parameters evaluated were: duration and viability of the larval stage, pupal stage duration and survival, adult longevity, reproductive period, post-reproductive and total number of eggs per female. The duration of the larval stage of C. sanguinea was lower when fed aphids reared on the cultivar NuOPAL, while adult longevity and the reproductive period were higher. The female fertility and egg viability were also lower.
Biological aspects of cycloneda sanguinea (coleoptera: Coccinellidae) feeding on aphids reared on transgenic cotton bollgard ®
Keywords: Biological control; Cry1ac; Ladybug; Predators; Transgenic plant